Time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS) using an ionic‐liquid primary ion beam source. (12th September 2014) - Fujiwara, Yukio; Saito, Naoaki; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; Yi, Keewook; Hong, Tae Eun
<x xml:space="preserve">Abstract</x> An orthogonal acceleration time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS) system has been developed using a prototype vacuum‐electrospay primary beam source that is capable of producing continuous ion beam of an ionic liquid. As a primary ion beam, an imidazolium ionic liquid, 1‐ethyl‐3‐methylimidazolium bis(trifluoromethanesulfonyl) amide (EMI‐TFSA), was electrosprayed at pressures around 2 × 10−4 Pa and a flow rate of 50 nL/min. Using the TOF‐SIMS system, three samples were analyzed: (i) EMI‐TFSA, (ii) an ammonium ionic liquid, N, N‐diethyl‐N‐methyl‐N‐(2‐methoxyethyl)ammonium bis(trifluoromethanesulfonyl) amide (DEME‐TFSA), and (iii) a polyethylene glycol (PEG300). Preliminary data showed that the vacuum electrospray of the ionic liquid was applicable to a primary ion beam source for SIMS. Nevertheless, irradiation of the ionic‐liquid beam caused deposition as well as sputtering. The deposition would result from larger m/z components of ionic‐liquid charged droplets. This is because projectile energy per nucleon of the larger m/z components seems too low to sputter materials. Because m/z values of charged droplets decrease with decreasing flow rate, it is required to reduce the flow rate of the ionic liquid so as to suppress the deposition of the ionic‐liquid beam. Copyright © 2014 John Wiley & Sons, Ltd.